Changes in breast cancer management during the Corona Virus Disease 19 pandemic: An international survey of the European Breast Cancer Research Association of Surgical Trialists (EUBREAST) - Maria Luisa Gasparri; Oreste Davide Gentilini; Diana Lueftner; Thorsten Kuehn; Orit Kaidar-Person; Philip Poortmans (Breast, 2020)
Background: Corona Virus Disease 19 (COVID-19) had a worldwide negative impact on healthcare systems, which were not used to coping with such pandemic. Adaptation strategies prioritizing COVID-19 patients included triage of patients and reduction or re-allocation of other services. The aim of our survey was to provide a real time international snapshot of modifications of breast cancer management during the COVID-19 pandemic. Methods: A survey was developed by a multidisciplinary group on behalf of European Breast Cancer Research Association of Surgical Trialists and distributed via breast cancer societies. One reply per breast unit was requested. Results: In ten days, 377 breast centres from 41 countries completed the questionnaire. RT-PCR testing for SARS-CoV-2 prior to treatment was reported by 44.8% of the institutions. The estimated time interval between diagnosis and treatment initiation increased for about 20% of institutions. Indications for primary systemic therapy were modified in 56% (211/377), with upfront surgery increasing from 39.8% to 50.7% (p < 0.002) and from 33.7% to 42.2% (p < 0.016) in T1cN0 triple-negative and ER-negative/HER2-positive cases, respectively. Sixty-seven percent considered that chemotherapy increases risks for developing COVID-19 complications. Fifty-one percent of the responders reported modifications in chemotherapy protocols. Gene-expression profile used to evaluate the need for adjuvant chemotherapy increased in 18.8%. In luminal-A tumours, a large majority (68%) recommended endocrine treatment to postpone surgery. Postoperative radiation therapy was postponed in 20% of the cases. Conclusions: Breast cancer management was considerably modified during the COVID-19 pandemic. Our data provide a base to investigate whether these changes impact oncologic outcomes.